구강 근기능 운동프로그램이 노인의 구강 근기능 개선에 미치는 효과 - Ji-ae Nam; Ae-jin Jeong; Jung-hwa Lee (Han'guk Ch'iwisaeng Hakhoe chi, 2025)
연구목적: 본 연구는 실리콘 빨대 물기와 하모니카 연주를 포함한 구강 근기능 운동프로그램이 노인의 구강 근기능 향상에 미치는 효과를 확인하고자 하였다. 연구방법: 2022년 6월부터 10월까지 약 4개월간 경상북도 Y시의 노인복지관 이용 노인 37명을 대상으로 하였으며, 실험군(n=20)은 주 2회, 총 8주간 구강 근기능 운동프로그램에 참여하였고, 대조군(n=17)은 참여하지 않았다. 구강 근기능 평가는 중재전, 4주 후, 8주 후 총 3회 실시하였으며, 평가 항목은 교합력, 혀 근력, 최대 개구량, 조음 교대 운동으로 구성되었다. 연구결과: 구강 근기능 운동프로그램 적용 결과, 실험군은 대조군에 비해 교합력(p<0.01), 혀 근력(p<0.01), 최대 개구량(p<0.001), 조음 교대 운동(p<0.001)에서 통계적으로 유의한 향상을 보였다. 결론: 실리콘 빨대 물기와 하모니카 연주를 활용한 구강 근기능 운동프로그램은 노인의 구강 근기능(교합력, 혀 근력, 최대 개구량, 조음 교대 운동) 향상에 효과적인 것으로 나타났으며, 본 프로그램은 구강 근기능 증진을 위한 실천적 중재로서 향후 보건소 및 노인복지시설의 구강건강증진 프로그램에 보완적으로 적용할 수 있을 것으로 기대된다. Objectives: The aim of this was to evaluate the effects of an oral myofunctional exercise program on improving oral function in older adults who use welfare tubes. Methods: We recruited 37 older adults who had used the Gyeongbuk Community Welfare Center for approximately four months between June and October 2022. The control group completed a questionnaire and an objective oral myofunction assessment, whereas the experimental group participated in an oral myofunction exercise program. The program was conducted twice weekly for 8 weeks at a community center. Objective oral health assessments were performed in both groups before, during, and after, 4 and 8 weeks after the start of the intervention period. Results: As a result of the oral myofunctional exercise program, a comparison of the subjects bite force (p=0.008), tongue pressure (p=0.003), maximum mouth opening (p<0.001), and alternating Diadochokinesis (DDK) (p<0.001) showed that the experimental group had greater improvements than the control group. Conclusions: Based on these findings, oral myofunctional exercise-such as chewing silicone straws and playing harmonica-should be incorporated into the existing oral health programs in public health centers and welfare facilities for older adults.